2012
DOI: 10.1371/journal.pone.0036833
|View full text |Cite
|
Sign up to set email alerts
|

A General Strategy to Endow Natural Fusion-protein-Derived Peptides with Potent Antiviral Activity

Abstract: Fusion between the viral and target cell membranes is an obligatory step for the infectivity of all enveloped virus, and blocking this process is a clinically validated therapeutic strategy.Viral fusion is driven by specialized proteins which, although specific to each virus, act through a common mechanism, the formation of a complex between two heptad repeat (HR) regions. The HR regions are initially separated in an intermediate termed “prehairpin”, which bridges the viral and cell membranes, and then fold on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 62 publications
6
88
0
Order By: Relevance
“…The HPIV3-derived dimeric peptide [VG PEG4 ] 2 -chol, despite being the most potent of the HPIV3-derived peptides at inhibiting MV fusion, did not block infection in vivo. These results suggest that, unlike NiV and HPIV3 infections, which can both be inhibited by the same HPIV3 HRC peptides (51,58), inhibition of MV requires a sequence specifically derived from its own F protein. In the future, "cocktails" of antiviral peptides may be a useful approach to achieving a broad-spectrum coverage.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The HPIV3-derived dimeric peptide [VG PEG4 ] 2 -chol, despite being the most potent of the HPIV3-derived peptides at inhibiting MV fusion, did not block infection in vivo. These results suggest that, unlike NiV and HPIV3 infections, which can both be inhibited by the same HPIV3 HRC peptides (51,58), inhibition of MV requires a sequence specifically derived from its own F protein. In the future, "cocktails" of antiviral peptides may be a useful approach to achieving a broad-spectrum coverage.…”
Section: Discussionmentioning
confidence: 91%
“…Since we expect our proposed antiviral strategy to be host factor independent, it will fill a specific need for immunocompromised people at risk for MV infection, who cannot be vaccinated or do not respond adequately to vaccine. We have previously shown that HPIV3 HRC-derived peptides are effective inhibitors of viral entry for other paramyxoviruses as well, including Hendra virus, Nipah virus, and simian virus 5 (SV5 or PIV5) (51,58,59), raising the possibility of broad-spectrum antivirals. We therefore tested their efficacy against the MV fusion machinery in vitro and against MV infection in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used structure-based design to improve the strength of the peptide-target interaction, and we conjugated a cholesterol group to the peptides to increase the inhibitor concentration at the location of receptor binding (30,31); in this way, we obtained a potent fusion inhibitor that prevented and treated lethal Nipah virus (NiV) encephalitis in vivo (30). Recently, we showed that peptide efficacy against NiV, human parainfluenza virus type 3 (HPIV3), and human immunodeficiency virus type 1 (HIV-1) can also be improved by combining cholesterol conjugation with dimerization of the HRC peptide (32). Here, we report that cholesterolconjugated dimeric HRC peptides derived from MV F can effectively inhibit MV fusion, block viral spread, and prevent MV infection both ex vivo in brain explants and in vivo in an established animal model of MV encephalitis.…”
mentioning
confidence: 99%